A large community outbreak of Legionnaires’ disease in Vila Franca de Xira, Portugal, October to November 2014 - Shivaji, Tara (2015)
An outbreak of Legionnaires’ disease with 334 confirmed cases was identified on 7 November 2014 in Vila Franca de Xira, Portugal and declared controlled by 21 November. Epidemiological, environmental and microbiological analysis identified industrial wet cooling systems to be the probable source of infection. Preliminary results from sequence-based typing of clinical specimens and environmental isolates confirmed this link. A series of meteorological phenomena are likely to have contributed to the scale of this outbreak.